Peningkatan Produksi dan Pembuatan Laporan Keuangan Jamu Herbal Keluarga Kolok di Desa Bengkala - Ni Putu Linda Santiari; Ramayasa, I Putu Ramayasa; Suwastika, I Wayan Kayun; Tokan, Sindyawati Rari Duli Goran (Sevanam: Jurnal Pengabdian Masyarakat, 2025)
Bengkala Village in Bali has a deaf community that has been part of the community for centuries. One of the businesses carried out by this community is the herbal medicine home industry. This study aims to increase the production of herbal medicine managed by the Kolok family in Bengkala Village. The main problems faced are limited production capacity and marketing that is still done manually. The solutions offered include providing production tools such as pans and blenders, as well as upgrading the packaging design by adding contact information and storage methods. In addition, financial report preparation training is also carried out to help business owners record raw materials, production costs, selling prices, and profit calculations more accurately. The results of the implementation of the activity are that partners have logos, packaging labels containing information about the products sold. In addition, partners are also able to make financial reports for each production. This activity is expected to increase the productivity and sustainability of the herbal medicine business, as well as provide a positive socio-economic impact on the Bengkala Village community.